The Effect of Liquid Organic Fertilizer (LOF) Made from Rabbit Urine and NPK Fertilizer on the Growth of Bok Choy (Brassica rapa L. Subsp. chinensis) - Legita Dwi Kurnianta; Prapti Sedijani; Ahmad Raksun (Jurnal Biologi Tropis, 2021)
Fertilizer is one of the most important needs for plants. Fertilizing can be done by using inorganic fertilizers or organic fertilizers. Long term fertilizing by using inorganic fertilizers without adding the organic matter could potentially reduce soil fertility and lead to not optimal growth of the plant. This study aims to determine the effect of liquid organic fertilizer (LOF) made from rabbit urine, NPK fertilizer, and the combination of both fertilizers on the growth of bok choy, and to determine the best fertilizer dosage for the growth of bok choy. This study uses a Completely Randomized Design consisting of 2 factors, the dose of rabbit urine LOF and dose of NPK fertilizer; 4 dosage levels each in triplicates. Data was analyzed using ANOVA followed by DMRT Test. The results indicates that the application of LOF made from rabbit urine, NPK fertilizer, and the combination of both fertilizers increasesÃÂ  plant height, leaves number, leaf area, wet weight, dry weight, and chlorophyll total of bok choy. DMRT (a 5%) test shows the best dosage applied for enhancing growth parameter are 6 ml of LOF plus 0,4 gram of NPK for plant height, wet weight, and dry weight, the 4 ml of LOF plus 0,6 gram of NPK for leaves number and leaf area, and the 4 ml of LOF plus 0,4 gram NPK for chlorophyll total.